(3QSGdI Edi CHj SYjO Hf CHj GdNjQ GdUhais - (3CHi SYjO Hf CHi GdNjQ GdUhais; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hUd cJGH GdTjN Yf Med UfGjY Gddg JYGdi hjhY fYeJg Ydjg hLRjd EMSGfg s
(3BNQgG (B:s
(3Cbhd bhdi gPG hCJhb Edjg hGSJcafg hCSCdg Gf jbQHfi Edjg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B841s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs